An experience of the treatment of a patient with chronic pancreatitis with pancreatic pleural fistula complicated by lung abscesses - N. Yu. Kokhanenko; A. A. Kashintsev; A. A. Bobylkov; R. G. Avanesyan; E. V. Shepichev; A. L. Ivanov; A. V. Glebova; O. G. Vavilova; K. V. Medvedev; L. A. Solovyova (Вестник хирургии имени И.И. Грекова)
Pancreatic pleural fistula is one of the rare and difficulty verifying complication of chronic pancreatitis. We present a rare medical case of a patient with chronic pancreatitis complicated by pancreatic pleural fistula with the formationof multiple lung abscesses. At the same time, the success of the treatment of the patient was due to the staged treatment and the participation of a multidisciplinary team of specialists.